Effect of Extraction And Nonextraction Treatment on Long Term Mandibular Incisors Stability - Şaziye Öner; Müyesser Saraç (Turkish Journal of Orthodontics, 2011)

(untitled)
Aim:To determine the effect of extraction or nonextraction treatment on long term mandibular incisors stability.Subjects and Methods:14 extraction (mean age: 14 years and 1 month) and 12 nonextraction (mean age:13 years and 2 months), total 26 patients (F:15, M:11) were selected from the archive of Dentistry Faculty of Istanbul University Department of Orthodontic. On pretreatment (T1), posttreatment (T2) and postretention (T3) digital models; intercanine width, intermolar width and Irregularity Index were measured by using Orthomodel version 1.0 program. Mean value of long-term irregularity index scores, transversal measurements and standart deviations were calculated for before treatment, after treatment and after postretention period. Mann-Whitney test was used to compare extraction and nonextraction groups.Results:In intercanine width; there was no statistically difference between groups in all periods (T1, T2, T3 and T3-T2). Intermolar width was decreased in extraction group but it was stable in nonextraction group after treatment. Irregularity index scores were statistically higher in extraction group at the begining of the treatment. But there was no difference between groups at the end of the treatment and after postretention period.Conclusion:In the comparison of extraction and nonextraction groups for the purpose of mandibular incisors irregularity and transversal measurements after treatment and long term postretention results, there was no difference between groups in terms of relapse. On this account, this study's findings suggested that extraction and nonextraction treatment protocols do not effect long term relapse.